“They're sleek, stylish and sexy:” selling e-cigarettes online - Riwu Bara, Roy Pefi; McCausland, Kahlia; Swanson, M.; Scott, L.; Jancey, Jonine (2023)
Objective: We examined the product range, marketing strategies, access and marketing claims made by Australian and New Zealand (NZ) online e-cigarette retailers. Methods: Twenty Australian (n=10) and NZ (n=10) e-cigarette retail websites were identified via Google using a combination of keywords nominated by an expert panel and identified via a literature review: ‘e-cigarette’, ‘e-cigs’, ‘vape’, and ‘vaping’, combined with ‘Australia’, ‘AU’, ‘New Zealand’ and ‘NZ’ and then examined. Results: Products were extensive (disposable, pod-based, reusable, replacement parts), 95% (n=19) offered ‘Starter Kits,’ flavoured e-liquid (n=1,032), most containing nicotine (70%, n=14). Most retailers (85%, n=17) offered price discounts and free delivery. There were unsubstantiated health claims (80%, n=16), cessation claims (65%, n=13) and cost-benefit claims (50%, n=10) promoting e-cigarette use. Most (n=14) website age verification features simply required the purchaser to indicate they were aged 18 years. Conclusions: Although e-cigarette regulations are different in Australia and NZ, the online product range, marketing strategies, access and marketing claims were similar and sold e-liquid containing nicotine. The health and cessation e-cigarette marketing claims were outlandish and unsubstantiated. Implications for public health: Most purchasing of e-cigarettes occurs online. Regulations and enforcement to limit access and stop unsubstantiated marketing claims must be a public health priority.